210Pb geochronology of sediments from the Guama River and Guajara Bay in the Amazon region, Belem, Brazil. (19th January 2010) - Dias, Fabiana F.; Taddei, Maria Helena T.; Nascimento, Suziane M.; Lafon, Jean-Michel
This study chronologically dated three sediment profiles collected at the mouth of the Amazon River using the 210Pb geochronology method. All profiles were sliced into 5 cm layers and analysed for radionuclides through gamma spectrometry. The results obtained dated the sediments as far back as 65 years. The sedimentation rate was also determined. A subsequent interpretation of the results provides information on pollutants present in sediment layers and infer possible contamination patterns by operating industries and anthropogenic activities in the area of the Amazon Hydrographic Basin.